Petri Nets and Bisimulations - Nielsen, Mogens; Winskel, Glynn (BRICS Report Series, 1994)
Several categorical relationships (adjunctions) between models for concurrency have been established, allowing the translation of concepts and properties from one model to another. The purpose of the present paper is twofold: firstly to present a central example of such a relationship (a coreflection between asynchronous transition systems and Petri nets), and secondly to illustrate its use by transferring to nets a general concept of bisimulation.